Transmen and transwomen in China: darkness and resilience - Xue, Yan, author; Kwiatkowski, Lynn, advisor; Snodgrass, Jeffrey, committee member; Daum, Courtenay, committee member (Colorado State University. Libraries, 2021)
Anthropologists have studied transgenderism in various cultures and societies; however, few of these studies investigate the topics of identity development, family lives, and transgender community engagement, and their interwoven relationships in a socialist society. In this research, I look at the lives of Chinese transgender people and aim to understand what roles the government, family and domestic transgender community institutions play in their identity development trajectory. I approach this main research question through a contextualized cultural perspective, analyze it within a critical-interpretive medical anthropological framework, and draw from both anthropological and non-anthropological literature that focus on these three themes. Research data is collected through a mixed qualitative methodology, including online and offline participant observation and semi-structured interviews of ten Chinese transwomen, ten Chinese transmen, and three key informants. Findings suggest that for Chinese transgender respondents, their trajectory of realizing, exploring, and living as their identified gender, which is different from their assigned sex/gender, is commonly repressed and stigmatized on an everyday basis within the cisgender male-female binary system in Chinese society. During these processes, acquiring family recognition and building community connection are respondents' vital sources of resilience, which not only consolidate their (trans)gender identification but also facilitate their transitions. Nevertheless, this is not to say that the family and community institutions are immune to the sexist ideology and cisgender prejudice circulating in Chinese society, which can generate distress mixed with their empowering influences on Chinese transgender respondents. Therefore, throughout their identity development trajectory, respondents always have to resort to their own agency to protect and emancipate themselves from both structural discrimination and transnormative discipline that operate within the institutions which are commonly expected to enhance the resiliency of transgender people.
Keywords: Chinese transgender studies; family lives; transgender identity development; critical-interpretive medical anthropology; Chinese transgender activism; transgender community engagement